Emptying the stores: lysosomal diseases and therapeutic strategies - Platt, F (Springer Nature, 2017)
Lysosomal storage disorders (LSDs) — designated as 'orphan' diseases — are inborn errors of metabolism caused by defects in genes that encode proteins involved in various aspects of lysosomal homeostasis. For many years, LSDs were viewed as unattractive targets for the development of therapies owing to their low prevalence. However, the development and success of the first commercial biologic therapy for an LSD — enzyme replacement therapy for type 1 Gaucher disease — coupled with regulatory incentives rapidly catalysed commercial interest in therapeutically targeting LSDs. Despite ongoing challenges, various therapeutic strategies for LSDs now exist, with many agents approved, undergoing clinical trials or in preclinical development.